2017
DOI: 10.1007/s00231-017-2137-x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of heat transfer for axisymmetric bubble impingement and rebound

Abstract: Heat transfer enhancement resulting from the impingement and rebound of bubbles in confined geometries can play an important role in heat transfer applications. Limited studies exist on the impact behaviour of large ellipsoidal bubbles against a horizontal surface, while the associated fluid flow field has received even less recognition. To address this, the current study investigates the dynamics of a single large ellipsoidal bubble impinging on a horizontal heated surface.The bouncing dynamics have been expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Donnelly et al , investigated the mechanism of enhancement effect of sliding bubble movement on the surface heat transfer by injecting gas at the bottom and controlled the heat transfer intensity by changing the angle of the heating surface. Enhanced heat transfer caused by two-phase flow also plays an important role in convection cooling, Donoghue et al , regulated the size and velocity of rising bubbles by changing the diameter and release distance of bottom injection orifice, thus controlling the bouncing behavior of bubbles on the horizontal heating surface and achieving the regulation of heat transfer enhancement. Morick et al studied the oscillatory motion of bubbles in a silicone oil system with temperature gradient and found that the diameter of the floating bubbles oscillated with time, leading to a change in the dominance between buoyancy and thermal Marangoni force.…”
Section: Introductionmentioning
confidence: 99%
“…Donnelly et al , investigated the mechanism of enhancement effect of sliding bubble movement on the surface heat transfer by injecting gas at the bottom and controlled the heat transfer intensity by changing the angle of the heating surface. Enhanced heat transfer caused by two-phase flow also plays an important role in convection cooling, Donoghue et al , regulated the size and velocity of rising bubbles by changing the diameter and release distance of bottom injection orifice, thus controlling the bouncing behavior of bubbles on the horizontal heating surface and achieving the regulation of heat transfer enhancement. Morick et al studied the oscillatory motion of bubbles in a silicone oil system with temperature gradient and found that the diameter of the floating bubbles oscillated with time, leading to a change in the dominance between buoyancy and thermal Marangoni force.…”
Section: Introductionmentioning
confidence: 99%